Ensino de língua portuguesa na perspectiva dos multiletramentos - Schwartz, Neandro (2023)
The National Common Curricular Base (BNCC) challenges us, as teachers, to think of a new teaching concept that effectively establishes a relationship between students' knowledge and social practices. Teaching and learning today presupposes an educational paradigm that considers connectivity, collaboration, interactivity and diversity (of technologies, languages, cultures) at school and, as an extension, in society. In this sense, studies of multiliteracies - which support the BNCC - can be configured as a support for classroom practices, providing teachers with alternatives to achieve changes in teaching. Thus, we seek, through the research on the screen, to develop and apply a didactic sequence for teaching and learning the Portuguese language in the light of precepts of multiliteracies, preparing students for new language practices. The guiding questions that guide the work are: what aspects need to be considered to carry out work based on multiliteracies precepts? What would a teaching and learning proposal based on such precepts look like? Seeking such answers, we substantiated and developed a practical proposal, applied to a 6th year elementary school class at a state school in Rondônia. It is, therefore, action research. The theoretical basis that underlies the proposal are, mainly, the studies of Magda Soares (2008), Angela Kleiman (2005), Roxane Rojo (2012), Lemke (2010) of the New London Group (2021), in addition to the Common National Base Curriculum (2018). The activities were developed in 9 meetings, totaling 18 class periods. The expected results were satisfactorily achieved. Regarding the reading of multisemiotic texts, the activities of analysis and discussion about the effects of meaning projected by the constituent elements, such as colors, shapes, the soundtrack, objects in the scenes, etc. It was innovative for the students and attracted a lot of attention. Also producing a multisemiotic text in a digital environment - students produced slides about comic strips and presented them to their colleagues - was a new practice for the students, who were excited and participative. The oral activities were also productive and brought the students' experiences into the classroom, encouraging debate about cultural aspects specific to the community and the students' personal experiences. Furthermore, through the proposed activities – more visual and interactive – it was also possible to observe greater participation from atypical students. Thus, the proposal developed based on the chosen textual genres fulfilled expectations, since, following precepts of the BNCC and multiliteracies, it was possible to articulate work around orality, reading, textual production and linguistic and semiotic analysis that promoted new knowledge to students, enabling them to take a leading role in activities